Community Prescribing and Resistant Streptococcus pneumoniae - Galia Barkai; David Greenberg; Noga Givon-Lavi; Eli Dreifuss; Daniel Vardy; Ron Dagan (Emerging Infectious Diseases, 2005)
We investigated the association between prescribing antimicrobial agents and antimicrobial resistance of Streptococcus pneumoniae among children with acute otitis media in southern Israel. During a 6-year period, all prescriptions of a sample of ≈20% of Jewish and Bedouin children <5 years of age were recorded and all pneumococcal isolates from middle ear fluid were collected. Although antimicrobial drug use was significantly higher in Bedouin children, the proportion of S. pneumoniae isolates with penicillin MIC ≥1.0 μg/mL was significantly higher in Jewish children. In both populations, antimicrobial prescriptions were markedly reduced over time, especially for penicillins and erythromycin. In contrast, azithromycin prescriptions increased from 1998 to 2001 with a parallel increase in macrolide and multidrug resistance. Penicillin resistance was associated with macrolide resistance. These findings strongly suggest that azithromycin affects increased antimicrobial resistance, including multidrug resistance, in S. pneumoniae.